Pengaruh Zikir Terhadap Kualitas Tidur Berdasarkan Sufi Healing - Metria Zeta; Nabilah Azzahrah Chaidir; Rafli Hanif Pambudi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Sleep is a basic need for everyone. The demands of work, college, and school make many people have poor sleep quality. According to the World Economic Forum, around 62% of adults around the world feel sleep-deprived. Lack of sleep can affect sleep quality. This can cause many problems in terms of health and academics for students. Sufi healing, or Sufi therapy, is spiritual therapy that includes dhikr. Dhikr itself is the repeated pronunciation of the words of Allah. In Islam, Sufi healing is in accordance with Islamic teachings. Many studies show that Sufi healing is good for patient therapy because dhikr can add positive value and relax the body. This research is quantitative, using a questionnaire. The questions are modified using the Pittsburgh Sleep Quality Index (PSQI). The respondents are medical students. Questions include feelings after and before sleeping after reading dhikr, feelings when sleeping, and level of sleep satisfaction. By comparing the quality of sleep before and after doing dhikr before bed, the results showed that there was a difference in sleep quality between after and before doing dhikr before bed. Most respondents felt that their sleep satisfaction was better if they did dhikr before going to bed.